Handbook of compliant mechanisms - Howell, Larry L.; Magleby, Spencer P.; Olsen, Brian M. [ (Brian Mark)] , 1983- (John Wiley & Sons, 2013)
A fully illustrated reference book giving an easy-to-understand introduction to compliant mechanisms A broad compilation of compliant mechanisms to give inspiration and guidance to those interested in using compliant mechanisms in their designs, the Handbook of Compliant Mechanisms includes graphics and descriptions of many compliant mechanisms